Positive electrode and non-aqueous electrolyte secondary battery
A balanced mixture of small solid and large hollow positive electrode active material particles in a non-aqueous electrolyte secondary battery addresses the trade-off between output and storage characteristics, enhancing both performance metrics.
Patent Information
- Application Number
- JP2023115642
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-14
AI Technical Summary
Existing non-aqueous electrolyte secondary batteries with hollow structured positive electrode active material particles face a trade-off between improved output characteristics and storage characteristics due to increased specific surface area leading to electrolyte reaction and gas entry.
A positive electrode comprising a mixture of solid first positive electrode active material particles with a small particle size and hollow second positive electrode active material particles with a large size, where the mass ratio of the first to second particles is controlled to achieve a balance between output and storage characteristics.
The solution enhances both output characteristics by shortening lithium diffusion distance and suppresses gas generation by reducing specific surface area, resulting in a non-aqueous electrolyte secondary battery with improved performance in both aspects.
Smart Images

Figure 2025012648000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] Positive electrode active material particles having a hollow structure are known as positive electrode active materials used in non-aqueous electrolyte secondary batteries. Positive electrode active material particles having a hollow structure have an increased specific surface area, and therefore, for example, improved output characteristics are expected. Patent Documents 1 and 2 disclose positive electrode active materials having a hollow structure. Patent Documents 3 and 4 disclose positive electrodes including positive electrode active material particles having a hollow structure and positive electrode active material particles having a solid structure. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-077577 A [Patent Document 2] International Publication No. 2014-181891 [Patent Document 3] JP 2017-123236 A [Patent Document 4] Patent Publication No. 2021-120937 Summary of the Invention [Problem to be solved by the invention]
[0004] However, while the output characteristics are improved by making the positive electrode active material particles have a hollow structure, the specific surface area of the positive electrode active material particles increases, which makes it easier for the electrolyte to react with the positive electrode active material particles, and makes it easier for gas to be generated inside the case. Therefore, a technology that can achieve both the output characteristics and the storage characteristics is desired.
[0005] Therefore, a main object of the present disclosure is to provide a technique capable of realizing a nonaqueous electrolyte secondary battery that combines excellent output characteristics and storage characteristics.
Means for Solving the Problem
[0006] One aspect of the technology disclosed herein is a positive electrode used in a non-aqueous electrolyte secondary battery. This positive electrode includes a current collector and an active material layer disposed on the surface of the current collector. The active material layer includes first positive electrode active material particles and second positive electrode active material particles. The first positive electrode active material particles have an average particle diameter based on the laser diffraction scattering method of 1 μm or more and 7 μm or less, and a porosity measured based on a cross-sectional SEM image of less than 10%. The second positive electrode active material particles include an outer shell portion and a hollow portion surrounded by the outer shell portion, have an average particle diameter based on the laser diffraction scattering method of 8 μm or more and 14 μm or less, and a ratio of voids measured based on a cross-sectional SEM image of 10% or more, and 80% or more of the voids are present inside the outer shell portion. The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula: 0 < M1 / (M1 + M2) ≤ 0.6.
[0007] Such a positive electrode includes first positive electrode active material particles that are relatively solid particles with few voids and second positive electrode active material particles that are relatively hollow particles with many voids. The first positive electrode active material particles having a solid structure are smaller in size than the second positive electrode active material particles and have a relatively small particle diameter (for example, 7 μm or less), so that the lithium diffusion distance in the first positive electrode active material particles is shortened, and thus the output characteristics of the secondary battery can be improved. In addition, the second positive electrode active material particles having a hollow structure are larger in size than the first positive electrode active material particles and have a relatively large particle diameter (for example, 8 μm or more), so that the specific surface area of the second positive electrode active material particles is reduced and gas generation can be suppressed, and thus the storage characteristics are improved. By adjusting the mixing ratio of such first positive electrode active material particles and second positive electrode active material particles to an appropriate range, a non-aqueous electrolyte secondary battery with excellent output characteristics and storage characteristics can be realized.
Brief Description of the Drawings
[0008] [Figure 1] FIG. 1 is a cross-sectional view schematically showing a positive electrode sheet according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic structure of a second positive electrode active material particle according to one embodiment. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates a schematic configuration of a lithium-ion secondary battery according to one embodiment. [Figure 4] FIG. 4 is a schematic exploded view showing the configuration of the wound electrode body. [Diagram 5] FIG. 5 is a schematic diagram showing the general configuration of a crystallizer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the technology disclosed herein will be described with reference to the drawings. Note that matters other than those specifically mentioned in this specification and necessary for implementing the present technology (for example, the general configuration and manufacturing process of a non-aqueous electrolyte secondary battery that does not characterize the present technology) can be understood as design matters of a person skilled in the art based on the conventional technology in the field. The present technology can be implemented based on the contents disclosed in this specification and the technical common sense in the field. Note that each drawing is drawn diagrammatically, and the dimensional relationship (length, width, thickness, etc.) does not necessarily reflect the actual dimensional relationship. In addition, in the drawings described below, the same reference numerals are given to members and parts that perform the same function, and duplicated descriptions may be omitted or simplified.
[0010] In this specification, when a numerical range is described as "A to B (where A and B are any numerical values)", it means "A or more and B or less", and also includes the meanings of "greater than A and less than B", "greater than A and B or less", and "greater than A and less than B".
[0011] In this specification, the term "non-aqueous electrolyte secondary battery" refers to an electricity storage device that uses a non-aqueous electrolyte as a charge carrier and can be repeatedly charged and discharged with the movement of the charge carrier between the positive and negative electrodes. Also, in this specification, the term "lithium ion secondary battery" refers to an electricity storage device that uses lithium ions as a charge carrier and realizes charging and discharging by the movement of charges associated with lithium ions between the positive and negative electrodes.
[0012] The positive electrode disclosed herein is used in a non-aqueous electrolyte secondary battery, and is preferably used in a lithium ion secondary battery. Hereinafter, one embodiment of the positive electrode disclosed herein will be specifically described with reference to FIG. 1. FIG. 1 is a cross-sectional view that shows a schematic cross-sectional view of a positive electrode sheet 50 according to this embodiment, taken along the thickness direction and the width direction. The positive electrode sheet 50 can be used as a positive electrode for a lithium ion secondary battery.
[0013] 1, the positive electrode sheet 50 includes a positive electrode current collector 52 and a positive electrode active material layer 54 disposed on the surface of the positive electrode current collector 52. Here, the positive electrode active material layer 54 is disposed directly on the surface of the positive electrode current collector 52, but it may be disposed indirectly. The positive electrode active material layer 54 may be provided on only one surface of the positive electrode current collector 52, or may be provided on both surfaces of the positive electrode current collector 52 as shown in FIG.
[0014] 1, at the end in the width direction of the positive electrode sheet 50, the positive electrode current collector 52 may be provided with a positive electrode current collector exposed portion 52a on which the positive electrode active material layer 54 is not provided. The positive electrode current collector exposed portion 52a can function as a current collector. In some embodiments, the positive electrode current collector exposed portion 52a may be provided at the end of the positive electrode current collector 52 processed into a tab shape.
[0015] In this embodiment, the shape of the positive electrode collector 52 is a foil (or sheet), but is not limited thereto. The positive electrode collector 52 may have various forms, such as a rod, a plate, or a mesh. As for the properties of the positive electrode collector 52, a metal with good conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.) can be used as in conventional lithium ion secondary batteries, and among them, aluminum is preferable. As the positive electrode collector 52, aluminum foil is preferable.
[0016] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 6 μm or more and 20 μm or less.
[0017] The positive electrode active material layer 54 includes first positive electrode active material particles 100 and second positive electrode active material particles 200 .
[0018] The first positive electrode active material particle 100 is a solid particle having a solid structure. In this specification, the term "solid particle" refers to a particle in which the ratio of voids (porosity) to the entire cross section of the particle in a cross-sectional SEM image is less than 10%.
[0019] The first positive electrode active material particle 100 has a porosity of less than 10%, preferably 7% or less, more preferably 5% or less, as measured by a cross-sectional SEM image. This can improve the capacity characteristics. In this specification, the "porosity" refers to the arithmetic average of the porosities of at least 100 randomly selected particles.
[0020] The shape of the first positive electrode active material particles 100 is not particularly limited, but may be, for example, spherical or approximately spherical. In some embodiments, the first positive electrode active material particles 100 may be of an irregular shape. In this specification, "substantially spherical" refers to a shape that can be regarded as a sphere as a whole, and the average aspect ratio based on a cross-sectional observation image by an electron microscope is approximately 1 to 2, preferably 1 to 1.5, and more preferably 1 to 1.2. In addition, in this specification, "aspect ratio" refers to the value obtained by dividing the long side of the rectangle that has the smallest area among the rectangles circumscribing the outline of the particle by the short side. In addition, "average aspect ratio" refers to the arithmetic average of the aspect ratios of at least 100 randomly selected particles.
[0021] The average particle diameter of the first positive electrode active material particles 100 is, for example, 1 μm or more, preferably 2 μm or more, and more preferably 3 μm or more. The average particle diameter of the first positive electrode active material particles 100 is, for example, 7 μm or less, preferably 6 μm or less, and more preferably 5 μm or less. The smaller the average particle diameter of the first positive electrode active material particles 100, which are solid particles, the shorter the lithium diffusion distance, and therefore the output characteristics of the secondary battery can be improved. In this specification, the term "average particle size" refers to a particle size (D50) corresponding to a cumulative 50% in a volume-based particle size distribution measured by a laser diffraction / scattering particle size analyzer.
[0022] The BET specific surface area of the first positive electrode active material particle 100 is, for example, 0.5 m 2 / g or more and 0.8m 2 / g or more, 1.5m 2 / g or more, or 1.8m 2 The BET specific surface area of the first positive electrode active material particles 100 is, for example, 3 m 2 / g or less, and 2.5m 2 / g or less, 2.4m 2 / g or less, 2.3m 2 / g or less, or 2.2m 2 / g or less. The higher the BET specific surface area, the more the output characteristics tend to improve, and the lower the BET specific surface area, the more the storage characteristics tend to improve. When the first positive electrode active material particles 100 have a BET specific surface area within the range defined by the above upper and lower limits, the balance between the output characteristics and the storage characteristics can be suitably adjusted, and the compatibility of the output characteristics and the storage characteristics can be realized at a higher level.
[0023] The first positive electrode active material particles 100 may be, for example, a lithium transition metal composite oxide, a lithium transition metal phosphate compound, etc. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, etc.
[0024] The lithium transition metal composite oxide is preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element, and specific examples thereof include lithium nickel-based composite oxides, lithium cobalt-based composite oxides, lithium manganese-based composite oxides, lithium nickel manganese-based composite oxides, lithium nickel cobalt manganese-based composite oxides, lithium nickel cobalt aluminum-based composite oxides, and lithium iron nickel manganese-based composite oxides.
[0025] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.
[0026] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO 4 ), lithium manganese phosphate (LiMnPO 4 ), lithium manganese iron phosphate, etc.
[0027] In this embodiment, the first positive electrode active material particle 100 is represented by the following general formula (i): Li d Ni (1-x-y-z) Co x Mn y A z O 2 (i) It has a composition represented by the following. However, in the general formula (i), it is assumed that 0 ≦ x ≦ 0.5, 0 ≦ y ≦ 0.5, 0 ≦ z ≦ 0.1, and 0.95 ≦ d ≦ 1.2. Further, in the general formula (i), A is one or more elements selected from the group consisting of Al, Ti, Zr, Nb, Mo, and W.
[0028] In some embodiments, the first positive electrode active material particles 100 contain at least Ni as a transition metal. That is, in such embodiments, the general formula (i) further satisfies x + y + z < 1.
[0029] In some embodiments, the proportion of Ni is higher than the total proportion of Co and Mn. That is, in the general formula (i), x + y + z < 0.5 may be satisfied.
[0030] In some embodiments, the first positive electrode active material particles 100 contain Ni, Co, and Mn. That is, in the general formula (i), 0 < x < 0.5 and 0 < y < 0.5 may be satisfied. Further, in some embodiments, 0 < x < 0.3 and 0 < y < 0.3 may be satisfied.
[0031] The second positive electrode active material particles 200 are hollow particles having a hollow structure. FIG. 2 is a cross-sectional view schematically showing the structure of the second positive electrode active material particles 200 according to the present embodiment. The second positive electrode active material particles 200 include an outer shell portion 210 and a hollow portion 220. As used herein, the "hollow particle" refers to a particle in which, in the cross-sectional SEM image of the particle, the proportion of the void portion is 10% or more with respect to the entire cross-section of the particle, and 70% or more of the voids are inside the particle rather than the outer shell portion.
[0032] The porosity measured by the cross-sectional SEM image of the second positive electrode active material particles 200 is, for example, 10% or more, preferably 20% or more, more preferably 25% or more. Thereby, since the specific surface area increases and Li ions are likely to react, the output characteristics can be improved.
[0033] The shape of the second positive electrode active material particles 200 is not particularly limited, but may be, for example, spherical or approximately spherical. In some embodiments, the second positive electrode active material particles 200 may be of an irregular shape.
[0034] The average particle diameter of the second positive electrode active material particles 200 is, for example, 8 μm or more, 9 μm or more, 10 μm or more, or 11 μm or more. The average particle diameter of the second positive electrode active material particles 200 is, for example, 14 μm or less, preferably 13 μm or less, and more preferably 12 μm or less. The larger the average particle diameter of the second positive electrode active material particles 200, which are hollow particles, the more the reactivity between the second positive electrode active material particles 200 and the electrolyte can be suppressed, so that gas generation tends to be suppressed and the storage characteristics of the secondary battery tend to be improved. The smaller the average particle diameter of the second positive electrode active material particles 200, the more the specific surface area increases, so that the output characteristics tend to be improved. By having the average particle diameter of the second positive electrode active material particles 200 within the range specified by the above upper and lower limits, the balance between the output characteristics and the storage characteristics is suitably adjusted.
[0035] The outer shell 210 includes a plurality of primary particles 212. In this embodiment, the outer shell 210 is formed by agglomerating the plurality of primary particles 212 by physical or chemical bonding force. In this specification, the term "primary particle" refers to the smallest unit constituting a positive electrode active material particle, and specifically refers to the smallest unit determined from the geometric shape of its appearance.
[0036] The outer shell 210 may have a single-layer structure, or may have a multi-layer structure in which multiple layers are stacked.
[0037] The average thickness of the outer shell 210 may be, for example, 1 / 5 or less, and preferably 1 / 6 or less, of the average particle diameter of the second positive electrode active material particles 200. The average thickness of the outer shell 210 may be, for example, 1 / 10 or more, or 1 / 8 or more, of the average particle diameter of the second positive electrode active material particles 200. By making the average thickness of the outer shell 210 thinner than the average particle diameter of the second positive electrode active material particles 200, the diffusion resistance of Li ions is reduced and the output characteristics are improved. In this specification, the thickness of the outer shell 210 refers to that measured in a cross-sectional observation image of the second positive electrode active material particle 200 taken by an electron microscope, and the average thickness of the outer shell 210 refers to the arithmetic mean of the thicknesses of the outer shell 210 measured in at least 100 second positive electrode active material particles 200.
[0038] The shape of the primary particles 212 may be, for example, needle-like, plate-like, elliptical, or the like. The average aspect ratio (length of major axis / length of minor axis) of the second positive electrode active material particles 200 based on a cross-sectional observation image of the second positive electrode active material particles 200 with an electron microscope is, for example, 2 or more, preferably 3 or more, and more preferably 5 or more. The longer the average aspect ratio of the primary particles 212, the more the diffusion resistance of Li ions can be reduced. The average aspect ratio of the primary particles 212 may be, for example, 50 or less, 20 or less, or 10 or less.
[0039] The average length of the major axis of the primary particles 212 is, for example, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, or 0.3 μm or more, and the average length of the major axis of the primary particles 212 is, for example, 1.2 μm or less, 1 μm or less, or 0.8 μm or less.
[0040] The average length of the minor axis of the primary particles 212 is, for example, 0.01 μm or more, 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more, and the average length of the minor axis of the primary particles 212 is, for example, 0.6 μm or less, 0.4 μm or less, or 0.2 μm or less.
[0041] The average lengths of the major and minor axes of the primary particles 212 are measured based on an electron microscope cross-sectional observation image of the second positive electrode active material particles 200. In this specification, the average lengths of the major and minor axes of the primary particles 212 refer to the arithmetic average of the major and minor axes of at least 100 primary particles 212.
[0042] At least 40% of the primary particles 212 contained in the outer shell 210 are radially oriented from the center of the second positive electrode active material particle 200 toward the surface of the second positive electrode active material particle 200. In a preferred embodiment, the oriented primary particles 212 account for at least 45%, at least 55%, at least 65%, or at least 70% of the primary particles 212. As more primary particles 212 are radially oriented, the flexibility of the second positive electrode active material particle 200 is improved and the particle is less likely to be broken. The ratio of the primary particles 212 mentioned above indicates a ratio based on the number, and indicates the ratio of the number of the primary particles 212 oriented radially out of the total number (at least 100) of the measured primary particles 212. In this specification, "primary particles are radially oriented" means that the angle formed by the long axis direction of the primary particle 212 with respect to a reference line connecting the center of the primary particle 212 and the center of the second positive electrode active material particle 200 is 30° or less. Note that such measurement can be performed by processing a cross section of the second positive electrode active material particle 200 with an ion beam and observing the cross section with an electron microscope. Note that as another method, the orientation can also be confirmed by electron backscatter diffraction (EBSD).
[0043] The hollow portion 220 is a space surrounded by the outer shell portion 210. The hollow portion 220 does not have to be completely surrounded by the outer shell portion 210, and includes an embodiment in which a part of the outer shell portion 210 is missing. In a preferred embodiment, the number of primary particles in the hollow portion 220 is less than that in the outer shell portion 210, or there are no primary particles in the hollow portion 220. That is, the ratio of the primary particles 212 contained in the outer shell portion 210 to the primary particles contained in the entire second positive electrode active material particle 200 can be, for example, 90% or more, 95% or more, 98% or more, or 100%. This makes it possible to obtain an active material that reacts well with Li during firing. In this specification, the proportion of such primary particles is measured based on the area ratio in a cross-sectional SEM.
[0044] The composition of the second positive electrode active material particles 200 may be the same as that of the first positive electrode active material particles 100 described above. The first positive electrode active material particles 100 and the second positive electrode active material particles 200 may have the same composition or may have different compositions. In a preferred embodiment, the second positive electrode active material particles 200 are a lithium transition metal composite oxide containing at least lithium and nickel.
[0045] In the present embodiment, the second positive electrode active material particles 200 are a lithium transition metal composite oxide containing lithium and a transition metal, and have a composition represented by the above general formula (i).
[0046] In some embodiments, the second positive electrode active material particles 200 contain Ni, Co, and Mn. That is, in the general formula (i), 0 < x < 0.5 and 0 < y < 0.5 can be satisfied. Also, in some embodiments, 0 < x < 0.3 and 0 < y < 0.3 can be satisfied.
[0047] In the embodiment shown in FIG. 2, the second positive electrode active material particles 200 include an outer shell portion 210 and a hollow portion 220, but in other embodiments, they may further include a central portion formed by aggregation of primary particles. The central portion is located inside the outer shell portion. A space where no primary particles exist may be provided between the central portion and the outer shell portion. Also, the central portion may have a solid structure or a hollow structure.
[0048] The ratio of the first positive electrode active material particles 100 and the second positive electrode active material particles 200 contained in the positive electrode active material layer 54 is, for example, when the mass of the first positive electrode active material particles 100 is M1 and the mass of the second positive electrode active material particles 200 is M2, the formula: 0 < M1 / (M1 + M2) ≤ 0.6 is satisfied. Also, M1 / (M1 + M2) is preferably 0.05 or more, more preferably 0.1 or more. Also, M1 / (M1 + M2) is preferably 0.3 or less, more preferably 0.2 or less. Thereby, the balance between the first positive electrode active material particles 100 which are solid particles and the second positive electrode active material particles 200 which are hollow particles becomes suitable, and both the output characteristics and the storage characteristics are favorably exhibited.
[0049] The total proportion of the first positive electrode active material particles 100 and the second positive electrode active material particles 200 contained in the positive electrode active material layer 54 is preferably 80 wt% or more, more preferably 85 wt% or more, and even more preferably 95 wt% or more of the entire positive electrode active material layer 54. Although not particularly limited, the total proportion of the first positive electrode active material particles 100 and the second positive electrode active material particles 200 contained in the positive electrode active material layer 54 can be 99 wt% or less of the entire positive electrode active material layer 54.
[0050] The positive electrode active material layer 54 may further include a conductive material, a binder, and the like. As the conductive material, for example, carbon black such as acetylene black (AB) or other carbon materials (carbon nanotubes, graphite, and the like) may be suitably used. As the binder, for example, polyvinylidene fluoride (PVDF) or the like may be used. Although not particularly limited, the proportion of the conductive material is, for example, 5 wt% or less, preferably 3 wt% or less, and more preferably 1 wt% or less of the entire positive electrode active material layer 54. In addition, although not particularly limited, the proportion of the binder is, for example, 5 wt% or less, preferably 3 wt% or less, and more preferably 1 wt% or less of the entire positive electrode active material layer 54.
[0051] The positive electrode sheet 50 can be produced according to a known method. Specifically, for example, a slurry containing the components of the positive electrode active material layer 54 is prepared. This slurry is applied onto the positive electrode current collector 52 and dried to form the positive electrode active material layer 54 on the positive electrode current collector 52. If necessary, the positive electrode active material layer 54 may be subjected to a press treatment.
[0052] The first positive electrode active material particles and the second positive electrode active material particles used in the present technology may be commercially available products, or may be processed or manufactured according to a known method. An example of a method for manufacturing the above-mentioned second positive electrode active material particles 200 will be described in the test example described later.
[0053] In the positive electrode sheet 50 according to the present embodiment, the first positive electrode active material particles 100 having a solid structure are smaller in size than the second positive electrode active material particles 200, and have a relatively small particle size (for example, 7 μm or less). This shortens the lithium diffusion distance in the first positive electrode active material particles 100, and therefore the output characteristics of the secondary battery can be improved. In addition, the second positive electrode active material particles 200 having a hollow structure are larger in size than the first positive electrode active material particles 100, and have a relatively large particle size (for example, 8 μm or more). This reduces the specific surface area of the second positive electrode active material particles 200, and suppresses gas generation, thereby improving storage characteristics. By adjusting the mixing ratio of such first positive electrode active material particles 100 and second positive electrode active material particles 200 to an appropriate range (for example, more than 0 and 0.6 or less), a nonaqueous electrolyte secondary battery that combines excellent output characteristics and storage characteristics can be realized.
[0054] Hereinafter, a nonaqueous electrolyte secondary battery including a positive electrode sheet 50 will be described using a lithium ion secondary battery as an example. FIG. 3 is a cross-sectional view that shows a schematic configuration of a lithium ion secondary battery 1 according to an embodiment. The lithium ion secondary battery 1 in FIG. 3 is a sealed battery in which a flat wound electrode body 20 and a nonaqueous electrolyte (not shown) are housed in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The positive and negative electrode terminals 42, 44 are electrically connected to the positive and negative electrode current collector plates 42a, 44a, respectively. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum.
[0055] FIG. 4 is a schematic exploded view showing the configuration of the wound electrode body 20. As shown in FIGS. 3 and 4, the wound electrode body 20 has a configuration in which the above-mentioned positive electrode sheet 50 and negative electrode sheet 60 are overlapped with two long separators 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode current collector exposed portion 52a and the negative electrode current collector exposed portion 62a (i.e., portions where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode current collector exposed portion 52a and the negative electrode current collector exposed portion 62a are joined to the positive electrode current collector plate 42a and the negative electrode current collector plate 44a, respectively.
[0056] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be a known negative electrode current collector used in lithium ion secondary batteries, for example, a sheet or foil made of a metal with good conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil or the like is preferable as the negative electrode current collector 62. The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined according to the battery design. When copper foil is used as the negative electrode current collector 62, its thickness is not particularly limited, but is, for example, 5 μm to 35 μm, and preferably 7 μm to 20 μm.
[0057] The negative electrode active material layer 64 includes a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, or soft carbon can be used. The negative electrode active material layer 64 can further include a binder, a thickener, and the like. As the binder, for example, styrene butadiene rubber (SBR) can be used. As the thickener, for example, carboxymethyl cellulose (CMC) can be used.
[0058] As the separator 70, various porous sheets similar to those conventionally used in lithium ion secondary batteries can be used, and examples thereof include porous resin sheets made of resins such as polyethylene (PE) and polypropylene (PP). Such porous resin sheets may have a single-layer structure or a multi-layer structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator 70 may be provided with a heat-resistant layer (HRL).
[0059] The non-aqueous electrolyte can be the same as that used in conventional lithium ion secondary batteries, and typically, a supporting salt can be contained in an organic solvent (nonaqueous solvent). As the non-aqueous solvent, aprotic solvents such as carbonates, esters, and ethers can be used. Among them, carbonates are preferred because they have a particularly high effect of reducing low-temperature resistance due to the positive electrode material. Examples of carbonates include ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such non-aqueous solvents can be used alone or in appropriate combination of two or more. As the supporting salt, for example, LiPF 6 , LiBF 4 A lithium salt such as lithium bis(fluorosulfonyl)imide (LiFSI) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0060] The nonaqueous electrolyte may contain components other than the nonaqueous solvent and supporting salt described above, such as various additives such as a gas generating agent, a film forming agent, a dispersing agent, and a thickener, as long as the effects of the present invention are not significantly impaired.
[0061] As an embodiment, a square lithium ion secondary battery having a flat wound electrode body has been described above. However, the lithium ion secondary battery can also be configured as a lithium ion secondary battery having a laminated electrode body (i.e., an electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The lithium ion secondary battery can also be configured as a cylindrical lithium ion secondary battery, a laminated case type lithium ion secondary battery, etc. Furthermore, an all-solid-state secondary battery using a solid electrolyte can also be constructed.
[0062] The lithium ion secondary battery 1 can be used for various applications. Suitable applications include a driving power source mounted on vehicles such as an electric vehicle (BEV; Battery Electric Vehicle), a hybrid electric vehicle (HEV; Hybrid Electric Vehicle), and a plug-in hybrid electric vehicle (PHEV; Plug-in Hybrid Electric Vehicle). The lithium ion secondary battery 1 can also be used as a storage battery for a small power storage device or the like. The lithium ion secondary battery 1 can also be used in the form of a battery pack in which a plurality of lithium ion secondary batteries 1 are connected in series and / or parallel.
[0063] As described above, specific aspects of the technology disclosed herein include those described in the following sections. Item 1: A positive electrode for use in a non-aqueous electrolyte secondary battery, A current collector; an active material layer disposed on a surface of the current collector; Equipped with the active material layer includes first positive electrode active material particles and second positive electrode active material particles, The first positive electrode active material particles include The average particle size based on a laser diffraction scattering method is 1 μm or more and 7 μm or less, The porosity measured based on cross-sectional SEM images is less than 10%; The second positive electrode active material particles include The container has an outer shell and a hollow portion surrounded by the outer shell, Based on the laser diffraction scattering method, the average particle size is 8 μm or more and 14 μm or less, the ratio of voids measured based on the cross-sectional SEM image is 10% or more, 80% or more of the voids are present inside the outer shell portion, the mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula: a positive electrode that satisfies 0 < M1 / (M1 + M2) ≤ 0.6. Item 2: The BET specific surface area of the first positive electrode active material particles is 1.5 m 2 / g or more and 2.3 m 2 / g or less. The positive electrode according to Item 1. Item 3: The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles satisfy the following formula: 0 < M1 / (M1 + M2) ≤ 0.2. The positive electrode according to Item 1 or 2. Item 4: 90% or more of the primary particles contained in the entire second positive electrode active material particles are present in the outer shell portion. The positive electrode according to any one of Items 1 to 3. Item 5: 40% or more of the primary particles present in the outer shell portion have an angle of 30° or less formed by the major axis direction of the primary particles with respect to the reference line connecting the center of the primary particles and the center of the second positive electrode active material particles. The positive electrode according to any one of Items 1 to 4. Item 6: The first positive electrode active material particles and the second positive electrode active material particles each have a general formula: Li d Ni (1-x-y-z) Co x Mn y A z O 2 (However, 0 ≤ x ≤ 0.5, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.1, 0.95 ≤ d ≤ 1.2, A is one or more additive elements selected from the group consisting of Al, Ti, Zr, Nb, Mo, and W) and are compounds represented by. The positive electrode according to any one of Items 1 to 5. Item 7: A non-aqueous electrolyte secondary battery including the positive electrode according to any one of Items 1 to 6.
[0064] Test examples relating to the present technology will be described below, however, the present technology is not limited to those shown in the following test examples.
[0065] [Preparation of hollow-structured positive electrode active material particles] A crystallizer capable of generating Taylor vortexes in a reaction chamber 330 was used. FIG. 5 shows the general configuration of the crystallizer 300 used. As shown in FIG. 5, the crystallizer 300 includes a cylindrical outer cylinder 310, a cylindrical inner cylinder 320 arranged coaxially with the outer cylinder 310, and a motor 322 connected to the inner cylinder 320. The inner cylinder 320 has a smaller diameter than the outer cylinder 310. The crystallizer 300 has a reaction chamber 330 between the outer cylinder 310 and the inner cylinder 320. The reaction chamber 330 is a region where a crystallization reaction is performed, and is a region where Taylor vortexes 332 and 334 are generated. The Taylor vortex refers to the flow of a fluid that generates a Taylor vortex. The Taylor vortex refers to a form of a vortex that flows in a circular shape.
[0066] As an example of the preparation of hollow-structured positive electrode active material particles, first, an oxygen concentration of 25 vol% was set in a 0.1 L reaction chamber 330, 1 wt% ammonia water was added, and the inner cylinder 320 was rotated around its axis at a rotation speed of 2000 rpm to generate Taylor vortexes in the ammonia water in the reaction chamber 330. Although only a portion of the Taylor vortexes 332 and 334 are shown in FIG. 5, Taylor vortexes were generated throughout the reaction chamber 330. Next, a 30 wt% aqueous sodium hydroxide solution was supplied to the reaction chamber 330, and the mixed liquid in the reaction chamber 330 was adjusted to pH 12 based on a liquid temperature of 25°C. Nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in water to prepare a 1 mol / L aqueous solution of raw metals, with a molar ratio of nickel sulfate:cobalt sulfate:manganese sulfate of 60:20:20. The raw metal aqueous solution, 1 wt % ammonia aqueous solution, and 30 wt % sodium hydroxide aqueous solution were respectively supplied from first supply port 312, second supply port 314, and third supply port 316 to the mixed liquid in which Taylor vortexes were generated in the reaction chamber 330 so as to have a volumetric ratio of 1:1:1, and crystallization was carried out for 30 minutes under a condition of pH 12. Thereafter, the crystallized product was taken out from discharge port 318, washed with water, filtered, and dried to obtain a powdered composite hydroxide (precursor). The composite hydroxide obtained above was analyzed by ICP emission spectroscopy. 0.6 Co 0.2 Mn 0.2 (OH) 2 It was confirmed that.
[0067] A lithium compound was mixed with the composite hydroxide so that the molar ratio (Li:M) of lithium (Li) to a metal element other than lithium (M) was 1.1:1. This mixture was held in a sintering furnace at 700°C under an oxidizing atmosphere for 5 hours and sintered. This resulted in a positive electrode active material. The positive electrode active material thus obtained was used as the second active material in some of the following examples.
[0068] [Measurement of the average particle size of positive electrode active material particles] The average particle size of the positive electrode active material was evaluated as the particle size (D50) corresponding to a cumulative 50% in the volume-based particle size distribution measured by a laser diffraction scattering type particle size analyzer.
[0069] [Evaluation of the structure of the positive electrode active material] In order to observe the cross-sectional shape of the positive electrode active material particles, the positive electrode active material particles were processed by an ion beam, and SEM images of the cross-sectional shape of the positive electrode active material particles were obtained. Based on the SEM images, the proportion of voids (proportion of the voids in the cross-sectional area of the particle) and their distribution were measured. Those with a void ratio of less than 10% were considered to have a solid structure. Those with a void ratio of 10% or more and 80% or more of the voids located inside the outer shell were considered to have a hollow structure. It was confirmed that the positive electrode active material particles obtained by the above-mentioned method involving Taylor vortices have an outer shell and a hollow portion surrounded by the outer shell, have a porosity of 25% or more, and on the cross-section of the particle, 90% or more of the primary particles constituting the particle are present in the outer shell.
[0070] [Evaluation of the orientation rate of hollow-structured positive electrode active material] For hollow-structured positive electrode active material particles, the orientation of the primary particles contained in the outer shell was confirmed by SEM observation of the particle cross section. Specifically, primary particles were evaluated as being radially oriented when the angle between the long axis direction of the primary particle and the reference line connecting the center of the primary particle and the center of the positive electrode active material particle was 30° or less. More than 100 primary particles contained in the outer shell were randomly observed, and the proportion of primary particles that were radially oriented (radial orientation rate) was calculated. The results are shown in Table 1. Cross-sectional SEM images were also taken of the precursor particles of the positive electrode active material particles, and it was confirmed that there was almost no change in the aspect ratio and orientation rate of the primary particles before and after firing.
[0071] [Measurement of BET specific surface area of positive electrode active material] The BET specific surface area of the positive electrode active material was measured using a flow type gas adsorption specific surface area measurement device.
[0072] Example 1 [Preparation of positive electrode plate (positive electrode sheet)] Average particle size: 3μm, BET specific surface area: 2.2m 2 The first active material had a solid structure of 1.0 μm / g, and the second active material had a hollow structure obtained by the above-mentioned method, with an average particle size of 12 μm and a radial orientation rate of 75%. The chemical formulas of both the first and second active materials were Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 O 2The positive electrode active material of Example 1 was prepared by mixing the first active material and the second active material in a mass ratio of 20:80. The positive electrode active material obtained above was mixed with N-methyl-2-pyrrolidone (NMP) in a ratio of 100:1:1 (by weight) of the conductive material and binder to prepare a positive electrode mixture paste. Acetylene black was used as the conductive material. PVDF was used as the binder. The prepared positive electrode mixture paste was applied to an aluminum foil of 13 μm and dried, and then pressed to a predetermined thickness and processed to a predetermined size to prepare a positive electrode plate.
[0073] [Preparation of negative electrode plate (negative electrode sheet)] The graphite, SBR, and CMC were mixed in water in a ratio of 100:1:1 (by weight) to prepare a negative electrode mixture paste. The prepared negative electrode mixture paste was applied to copper foil, dried, pressed to a specified thickness, and cut to a specified size to prepare a negative electrode plate.
[0074] [Preparation of non-aqueous electrolyte secondary battery] The prepared positive and negative electrode plates were stacked on top of each other with a separator interposed therebetween to prepare a laminated electrode body. Leads were attached to each of the positive and negative electrode plates. The prepared laminated electrode body was housed in an exterior body made of an aluminum laminate sheet, after which a non-aqueous electrolyte was poured in and the opening of the exterior body was sealed to prepare a test cell (laminate cell). The non-aqueous electrolyte was a solvent consisting of EC:FEC:EMC:DMC=15:5:40:40 (by volume) and 1M LiPF as a Li salt. 6 The following were used:
[0075] Example 2 Average particle size: 5μm, BET specific surface area: 1.8m 2 The first active material had a solid structure of 0.01g / g, and the second active material had a hollow structure obtained by the above-mentioned method, with an average particle size of 9μm and a radial orientation rate of 68%. The chemical formulas of both the first and second active materials are Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 O 2The first active material and the second active material were mixed at a mass ratio of 10:90 to obtain a positive electrode active material of Example 2. The subsequent procedures up to the preparation of a test cell were the same as those of Example 1.
[0076] Example 3 Average particle size: 5μm, BET specific surface area: 1.8m 2 A first active material having a solid structure of 1.0 μm / g and a second active material having a hollow structure with an average particle diameter of 10 μm were prepared. This second active material is composed of secondary particles formed by agglomeration of a plurality of primary particles. The secondary particles have a hollow center, a space outside the center where no primary particles are present, and an outer shell electrically connected to the center. The secondary particles had an average ratio of the outer diameter of the center to the particle diameter of the secondary particles of 30 to 80%. The primary particles constituting the outer shell of the secondary particles had a radial orientation ratio of 70%. The chemical formulas of both the first and second active materials are Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 O 2 The first active material and the second active material were mixed at a mass ratio of 10:90 to obtain a positive electrode active material of Example 3. The subsequent procedures up to the preparation of a test cell were the same as those of Example 1.
[0077] Example 4 Average particle size: 4μm, BET specific surface area: 0.8m 2 The first active material had a solid structure of 1.0 μm / g, and the second active material had a hollow structure of 12 μm average particle size and 65% radial orientation rate, obtained by the above method. The chemical formulas of both the first and second active materials were Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 O 2 The first active material and the second active material were mixed at a mass ratio of 20:80 to obtain a positive electrode active material of Example 4. The subsequent procedures up to the preparation of a test cell were the same as those of Example 1.
[0078] Example 5 Average particle size: 4μm, BET specific surface area: 2.4m 2 The first active material had a solid structure of 1.0 μm / g, and the second active material had a hollow structure of 12 μm average particle size and 65% radial orientation rate, obtained by the above method. The chemical formulas of both the first and second active materials were Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 O 2 The first active material and the second active material were mixed at a mass ratio of 60:40 to obtain a positive electrode active material of Example 5. The subsequent procedures up to the preparation of the test cell were the same as those of Example 1.
[0079] Comparative Example 1 Average particle size: 5μm, BET specific surface area: 2.4m 2 A first active material having a solid structure of 0.1 g / g and a second active material having a hollow structure with an average particle diameter of 5 μm were prepared. This second active material is composed of secondary particles formed by agglomeration of a plurality of primary particles. The secondary particles have a hollow center, a space outside the center where no primary particles are present, and an outer shell electrically connected to the center. The secondary particles had an average ratio of the outer diameter of the center to the particle diameter of the secondary particles of 30 to 80%. The primary particles constituting the outer shell of the secondary particles had a radial orientation ratio of 65%. The chemical formulas of both the first and second active materials are Li 1.1 Ni 0.6 Co 0.2 Mn 0.2 O 2 The first active material and the second active material were mixed at a mass ratio of 20:80 to obtain a positive electrode active material of Comparative Example 1. The subsequent procedures up to the preparation of a test cell were the same as those of Example 1.
[0080] Comparative Example 2 Average particle size: 10μm, BET specific surface area: 3.4m 2 The first active material had a solid structure of 1.0 μm / g, and the second active material had a hollow structure of 12 μm average particle diameter and a radial orientation rate of 55% obtained by the above method. The chemical formulas of both the first and second active materials were Li 1.1 Ni 0.6Co 0.2 Mn 0.2 O 2 Those represented by were used. They were mixed so that the mass ratio of the first active material to the second active material was 30:70, and used as the positive electrode active material of Comparative Example 2. The procedures up to the preparation of the test cell thereafter were the same as those in Example 1.
[0081] <Measurement of initial capacity> The test cell was charged by CCCV up to 4.2V in an environment of 25°C. The current value of the CC charge at this time was set to C / 3. Thereafter, it was discharged to 3V at a current value of C / 3. The discharge capacity at this time was defined as the initial capacity. Table 1 shows the results based on Comparative Example 1.
[0082] <IV resistance measurement> In an environment of 25°C, the test cell was charged so that the state of charge (SOC) became 50% and left standing for 1 hour. Thereafter, it was discharged at a current of 5C for 10 seconds. When the OCV voltage immediately before discharge was V0 and the voltage at the 10-second discharge time was V1, Formula: IV resistance = (V0 - V1) / 5C current value The IV resistance value was obtained according to. Table 1 shows the results at a ratio based on Comparative Example 1 described later.
[0083] <Measurement of gas generation amount> In an environment of 25°C, the test cell was charged by CCCV at a charging potential of 4.4V and a charging current of 0.3C. The charging was terminated when the charging current reached 0.01C. After charging, the test cell was placed in a constant temperature bath at 60°C and stored for 24 hours. Thereafter, the test cell was allowed to cool in a 25°C atmosphere. After cooling, the volume change of the test cell before and after storage was measured, and the gas generation amount (mL) during storage was determined. The volume of the test cell before or after storage was measured using Archimedes' principle, and the difference was taken as the gas generation amount.
[0084]
Table 1
[0085] <Evaluation of test example> Comparative Example 1 is a test example in which a secondary battery with low resistance and excellent output characteristics was realized by using relatively small hollow particles with an average particle diameter of 5 μm, but the amount of gas generated was large, leaving room for improvement in storage characteristics. Comparing Examples 1 to 5 with Comparative Example 1, as shown in Table 1, Examples 1 to 5 were able to reduce the amount of gas generated while maintaining the same resistance or further suppressing the resistance compared to Comparative Example 1. That is, it can be seen that in Examples 1 to 5, the storage characteristics were improved, and secondary batteries that achieved both excellent output characteristics and storage characteristics were realized.
[0086] Although specific examples of the present technology have been described above in detail, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above. [Explanation of symbols]
[0087] 1. Lithium-ion secondary battery 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet 52 Positive electrode current collector 52a Exposed part of positive electrode current collector 54 Cathode active material layer 60 Negative electrode sheet 62 Negative electrode current collector 62a Exposed part of negative electrode current collector 64 Negative electrode active material layer 70 Separator 100 First positive electrode active material particles 200 Second positive electrode active material particles 210 Outer shell 212 Primary particles 220 Hollow part 300 Crystallizer 310 Outer cylinder 320 Inner cylinder 330 Reaction Chamber
Claims
1. A positive electrode for use in a non-aqueous electrolyte secondary battery, A current collector; an active material layer disposed on a surface of the current collector; Equipped with the active material layer includes first positive electrode active material particles and second positive electrode active material particles, The first positive electrode active material particles include The average particle size based on a laser diffraction scattering method is 1 μm or more and 7 μm or less, The porosity measured based on a cross-sectional SEM image is less than 10%; The second positive electrode active material particles include The container has an outer shell and a hollow portion surrounded by the outer shell, The average particle size based on a laser diffraction scattering method is 8 μm or more and 14 μm or less, The ratio of voids measured based on a cross-sectional SEM image is 10% or more; 80% or more of the voids are present inside the outer shell portion, The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles are expressed by the following formula: A positive electrode that satisfies 0<M1 / (M1+M2)≦0.
6.
2. The first positive electrode active material particles have a BET specific surface area of 1.5 m 2 / g or more 2.3m 2 / g or less.
3. The mass M1 of the first positive electrode active material particles and the mass M2 of the second positive electrode active material particles are expressed by the following formula: The positive electrode according to claim 1 , wherein 0<M1 / (M1+M2)≦0.2 is satisfied.
4. The positive electrode according to claim 1 , wherein 90% or more of the primary particles contained in the whole of the second positive electrode active material particles are present in the outer shell portion.
5. 5. The positive electrode according to claim 4, wherein 40% or more of the primary particles present in the outer shell portion have an angle of 30° or less between a reference line connecting a center of the primary particle and a center of the second positive electrode active material particle and a longitudinal axis direction of the primary particle.
6. The first positive electrode active material particles and the second positive electrode active material particles each have a general formula: Li d Ni (1-x-y-z) Co x Mn y A z O 2 (wherein 0≦x≦0.5, 0≦y≦0.5, 0≦z≦0.1, 0.95≦d≦1.2, and A is one or more additional elements selected from the group consisting of Al, Ti, Zr, Nb, Mo, and W). The positive electrode according to claim 1 , wherein the compound is represented by the formula:
7. A non-aqueous electrolyte secondary battery comprising the positive electrode according to any one of claims 1 to 6.
Citation Information
Patent Citations
Positive electrode, preparation method thereof and lithium ion battery
CN114447273A
Nickel compound hydroxide and method for producing the same, positive pole active substance for nonaqueous electrolyte secondary cell and method for producing the same, and nonaqueous electrolyte secondary cell
JP2013147416A
Nonaqueous electrolyte secondary battery
JP2014011067A
Transition metal-containing composite hydroxide particle and manufacturing method therefor, cathode active material for nonaqueous electrolyte secondary battery and manufacturing method therefor, and nonaqueous electrolyte secondary battery
JP2019119662A
Positive electrode active material for lithium ion secondary battery, positive electrode and lithium ion secondary battery
JP2021120937A